2013
DOI: 10.1055/s-0033-1345198
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheits-Coaching in der Arbeitsmarktintegration – Evaluation eines Qualifizierungskonzepts

Abstract: Our results affirm the need for and prove the acceptance of education programmes enabling the pedagogic staff of job-training programmes to deliver health coaching. Periodic case conferences take into account the participants' request for more exchange of experiences, facilitate implementation and contribute to quality and sustainability. Further development of the education programme is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The process evaluation carried out as an integrated part of the study showed that the intervention was highly accepted by the professionals recruited as health coaches at both settings [ 14 ]. In total, 186 Motivational Interviews were performed at baseline and 119 after three months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process evaluation carried out as an integrated part of the study showed that the intervention was highly accepted by the professionals recruited as health coaches at both settings [ 14 ]. In total, 186 Motivational Interviews were performed at baseline and 119 after three months.…”
Section: Resultsmentioning
confidence: 99%
“…In the process evaluation of the “train-the-trainer” training program in our study, which was based on Kirkpatrick's four level training evaluation model, we did, however, see various positive indications of the cost-effectiveness of our approach [ 14 ]: a case report by one of the participating organizations of the secondary labor market in Munich reported a pronounced decrease in health-related days of absence among their unemployed clients (with a decrease to 4.5% in 2010, the year of the intervention, after levels of 20.4% in 2008 and 18.5% in 2009). Among the professionals trained as health coaches, 84% and 97%, respectively, stated that the techniques of Motivational Interviewing and participatory group sessions were helpful for their daily work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation